Safety outcomes of statin vs non-statin lipid-lowering interventions in patients with prior statin-associated muscle symptoms: A systematic review and meta-analysis - Philipp Stefan Aebi; Fanny Villoz; Jonas Bührer; Christina Lyko; Nazanin Abolhassani; Cinzia Del Giovane; Baris Gencer; Nicolas Rodondi; Manuel R. Blum (PLoS ONE, 2025)
Background Statin-associated muscle symptoms (SAMS) are an obstacle in the prevention of cardiovascular events. A systematic assessment of the evidence of interventions in the setting of SAMS is lacking. Objective To assess the evidence of strategies of statin-based vs non-statin based therapies in patients with a history of SAMS. Methods MEDLINE, EMBASE, Cochrane Central Register of Controlled Clinical Trials, Scopus, Clinicaltrials.gov and Proquest databases were searched from inception up to February 2024.We included randomized controlled trials (RCTs) and non-randomized studies involving patients with history of prior SAMS, comparing statin-based therapy to a comparator. We followed the PRISMA guideline with multiple authors involved at each stage. A random-effect model was used in the meta-analysis. We defined the primary outcome as incidence of muscle symptoms. The secondary outcomes were proportion of statin discontinuation of statin-based therapy within patients with history of SAMS. The protocol was registered on PROSPERO (CRD42020202619). Results In 23 studies (13 RCTs, 2 prospective and 8 retrospective studies) there were in total 1868 participants in RCTs and 47’628 participants in non-RCTs (follow-up 12 weeks – 31 months). Our confidence in the body of evidence using GRADE was moderate for the primary outcome and low-moderate for the secondary outcome. In RCTs among patients with history of SAMS, there was high heterogeneity in the statin regimens and controls (placebo/non-daily dosing/ezetimibe/PCSK9 inhibitors). In RCTs, the meta-analysis showed no difference between statin-based and control groups in the incidence of muscle symptoms (OR 1.19, 95%CI 0.86–1.64, I 2 : 46.3%)). Therapy discontinuation due to muscle symptoms in RCTs was higher in the statin-based than the comparator groups (OR 1.48, 95%CI 1.03–2.12, I 2 = 17.6%). Conclusion Our findings suggest that patients with a history of SAMS can be re-challenged with statins. More high-quality evidence is needed to strengthen guidelines regarding the management of SAMS.